Stagecraft and Statecraft: Advance and Media Events in Political Communication - Schill, Dan (Lexington Books, 2009)
Media events are a central communication tactic used by political communicators in political campaigns and in governmental affairs. Each president has an advance staff that creates mediagenic events to influence the news media, generate coverage and excitement, construct favorable political images, and persuade voters. Advance men and women are visual speechwriters who focus not only on what the politician says, but also on how the candidate looks and the visual message communicated by the event. This timely and groundbreaking work examines media events and advance in political communication by exploring: (1) how media events are conceived and staged, (2) the role of advance in an overall communication strategy, (3) how media events holistically function to generate a rhetorical impact, and (4) the implications of politically communicating by media event. This book gives readers the tools and background necessary to both analyze and understand media events and to create their own. Media events and advance are a significant element of political communication that has not been systematically or comprehensively studied, and Schill's innovative work ably fills this major gap in the literature.